Effect of Continuous Subcutaneous Injection of Insulin Analogues in Pregnant Women with Diabetes Mellitus Complicated with Ketoacidosis. (15th December 2021) - Pan, Yunfei; Wang, Qi; Zhao, Feimin; Shen, Jiaying; Zhong, Xiaojing
Abstract : Objective . To investigate the clinical effect of continuous subcutaneous injection of insulin analogues in pregnant women with diabetes mellitus complicated with ketoacidosis. Methods . A total of 92 pregnant patients with diabetes mellitus complicated with ketoacidosis from June 2014 to January 2021 were selected. All patients were randomly divided into an observation group and control group according to the method of random number. The control group received intravenous infusion of insulin, and the observation group received continuous subcutaneous infusion of quick-acting insulin analogues. The clinical effects of the two groups were observed. Results . The time needed to control blood glucose <13.8 mmol/L, the amount of insulin needed to control blood glucose <13.8 mmol/L, the time needed to correct DKA, and the amount of insulin needed to correct DKA in the observation group were significantly less than those in the control group (P < 0.05 ). Compared with the control group, the average occurrence times of hypoglycemia, the length of stay, the total amount of insulin in hospital, and the total amount of insulin used during pregnancy in the observation group were significantly less than those in the control group (P < 0.05 ). The values of SCr, CRP, BUN, arterial blood gas pH, and adiponectin in the two groups were significantly improved as compared with those before treatment, and the improvement in the observation group was significantly better than that in the control group (P < 0.05 ). After treatment, the fasting blood glucose, 2-hour postprandial blood glucose, carbon dioxide binding capacity, and glycosylated hemoglobin in the experimental group were significantly better than those in the routine group, and the difference was statistically significant (P < 0.05 ). Conclusion . Continuous subcutaneous injection of insulin analogues is effective in the treatment of diabetic patients with ketoacidosis, which can effectively improve blood glucose, carbon dioxide binding capacity, and glycosylated hemoglobin and accelerate the negative conversion of urinary ketone body. It is worth popularizing to reduce the occurrence of hypoglycemia and the dose of insulin and shorten the time of hospitalization.